2001
DOI: 10.1177/000456320103800511
|View full text |Cite
|
Sign up to set email alerts
|

Bilirubin Measured on a Blood Gas Analyser: A Suitable Alternative for Near-Patient Assessment of Neonatal Jaundice?

Abstract: The reliability of a recently released total bilirubin assay for a blood gas analyser was assessed in two Australian hospital laboratories. The instrument computes total bilirubin concentration from multi-wavelength absorbance measurements of undiluted whole blood or plasma. Performance of the Radiometer ABL 735 blood gas analyser bilirubin method (software version 3.6) was compared with a proven Roche diazo method for Hitachi analysers, calibrated using primary standards prepared from NIST SRM 916a bilirubin.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 9 publications
2
7
0
Order By: Relevance
“…Therefore, the requirement for sample preparation makes blood gas analyzers a more convenient choice. In this study, a statistically significant relationship was showed in ABL 735 blood gas analyzer and the Roche Cobas C8000 chemical analyzer as in the study by Peake et al (27). In the literature, many researchers have suggested that there is not a difference between the blood gas analyzer and the routine biochemistry analyzer.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Therefore, the requirement for sample preparation makes blood gas analyzers a more convenient choice. In this study, a statistically significant relationship was showed in ABL 735 blood gas analyzer and the Roche Cobas C8000 chemical analyzer as in the study by Peake et al (27). In the literature, many researchers have suggested that there is not a difference between the blood gas analyzer and the routine biochemistry analyzer.…”
Section: Discussionsupporting
confidence: 66%
“…For example, Rolinski et al concluded that the measurement of TB with the ABL 735 blood gas analyzer from whole blood samples was a promising method (28). Peake et al com-pared bilirubin results obtained on the Radiometer ABL 735 blood gas analyzer with Roche diazo method for Hitachi analyzers concluded that the Radiometer ABL 735 bilirubin assay was suitable for assessment of neonatal jaundice using whole blood, thus eliminating the need for sample centrifugation (27). There are many national and international studies comparing blood gas analyzer and biochemical autoanalyzer results, in a different source of fluid and electrolyte balance are searched (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Rolinski’s study (2001) showed bilirubin on ABL 735 ​= ​1.002 x (Hitachi 917) - 4.0 ​μmol/L, with 95% CI of slope 0.914–1.090, 95%CI of intercept −22–14 ​μmol/L [ 6 ]. Another study (Peake et al., 2001) showed bilirubin on ABL735 ​= ​0.986 x (Hitachi 917) - 0.4 ​μmol/L [ 5 ]. While conjugated and delta bilirubin were excluded, bilirubin on ABL735 ​= ​0.99 (Vitros 250) ​+ ​3.4 ​μmol/L [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some validation studies using neonatal whole blood samples provided conflicting correlations between blood gas analyzers and chemistry analyzers [ [5] , [6] , [7] , [8] , [9] ], which confused physicians in interpreting whole blood bilirubin results for patient management. The common causes of bias are a lack of standardized plasma bilirubin reference methods [ 10 , 11 ] and the difference in methodologies between blood gas analyzers using multiple-wavelength photometry and chemistry analyzers using diazo based assay [ [5] , [6] , [7] , [8] , [9] ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation